Predicting Factors of Joint Pain - Friska Sinaga; Lidwina Triastuti; Maria Yunita (Indonesian Journal of Applied Research (IJAR), 2021)
Joint pain could have impact on the wellbeing of elders with knee osteoarthritis (OA). Several factors could influence joint pain. Therefore, it is beneficial to explore contributing factors regarding with joint pain among Indonesian elders with knee osteoarthritis. The aim of this study was to explore predicting factors affecting joint pain of people with knee osteoarthritis. A descriptive cross sectional design was used and involved 100 participants. All participants were asked to answer the demographic questionnaire, Lifestyle Modification Behaviors Questionnaire (LMBQ), and Intermittent and Constant Osteoarthritis Pain (ICOAP). These instruments were validated by three experts. The internal consistency reliability of the LMBQ and ICOAP yielded a Cronbach Alpha coefficient of .84 and .95, respectively. The results indicated significant correlation between joint pain and age, body mass index, education, duration being diagnosed with OA , level of severity, and lifestyles modification behaviors. However, there was no significant difference between occupation, genders and joint pain. A multiple regression was conducted. Age, BMI, diseases duration, level severity of knee OA, and lifestyles behaviors were examined as predictors. These variables statistically significant predict join pain F (5.94) = 5.467, p< 0.001), R2=0.225. Age, gender, BMI, diseases duration, severity of knee OA, and lifestyle behaviors were related to joint pain. Therefore, nursing and other health professional should concern and consider these factors in allocating care to reduce joint pain in this group.